2013
DOI: 10.1097/sa.0b013e3182a49187
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Hormonal Stress Responses to Endotracheal Tube and ProSeal Laryngeal Mask Airway™ for Laparoscopic Gastric Banding

Abstract: T he increase in the number of morbidly obese patients undergoing surgery has prompted investigations into the most optimal anesthesia procedures for these individuals. Although the classic type of laryngeal mask airway is safe and efficacious in lean subjects, it has not been used often in obese patients because it provides only incomplete protection of upper airway against risk of aspiration and a limited range of positive-pressure ventilation. Stress responses from tracheal intubation can be dangerous in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 16 publications
0
24
1
Order By: Relevance
“…11 Similarly, Patel et al reported that there was rise in heart rate both during insertion and extubation in ETT group as compare to ProSeal LMA group and this change was highly significant,(P<0.01) The findings of Shroff et al, Carron et al and Kannan et al also concurred with present findings. 7,10,12,13 However, Lalwani et al and Dave et al found that heart rate was increased significantly in both ETT and PLMA group whereas in our study, HR is increased significantly in ETT group only. 14,15 This haemodynamic pressor response may be attributed to the sympathetic stimulation during laryngoscopy and intubation and this is due to sympathoadrenal response to tracheal intubation arises from stimulation of the pharyngeal wall and supraglottic region by tissue tension induced by laryngoscopy.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…11 Similarly, Patel et al reported that there was rise in heart rate both during insertion and extubation in ETT group as compare to ProSeal LMA group and this change was highly significant,(P<0.01) The findings of Shroff et al, Carron et al and Kannan et al also concurred with present findings. 7,10,12,13 However, Lalwani et al and Dave et al found that heart rate was increased significantly in both ETT and PLMA group whereas in our study, HR is increased significantly in ETT group only. 14,15 This haemodynamic pressor response may be attributed to the sympathetic stimulation during laryngoscopy and intubation and this is due to sympathoadrenal response to tracheal intubation arises from stimulation of the pharyngeal wall and supraglottic region by tissue tension induced by laryngoscopy.…”
Section: Discussioncontrasting
confidence: 51%
“…The reflex circulatory response is seen with an increase in the plasma catecholamine levels after laryngoscopy. 13 Among the catecholamine's, noradrenaline levels show a greater surge after laryngoscopy and intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carron et al, were able to achieve adequate gas exchange with PCV and I:E ratio of 1:1 in obese patients undergoing gastric banding while ventilating through a PLMA [67]. No hemodynamic instability was noted in any of these studies during PCV.…”
Section: Ventilation With Sad In Laparoscopic Surgerymentioning
confidence: 92%
“…Carron M et al, compared the hemodynamic and hormone stress response of PLMA and ETT in 70 morbidly obese pts (BMI > 30 kg/m 2 ) for laparoscopic banding surgery [67]. The study showed that there was significantly less hemodynamic and hormonal stress response with PLMA compared to ETT.…”
Section: Sad In the Obese Patientmentioning
confidence: 99%